Impact of tumor location on oncological and perioperative outcomes after robot-assisted radical nephroureterectomy for upper tract urothelial carcinoma - Mahmoud Farzat; Ibrahim Altaie; Sami-Ramzi Leyh-Bannurah; Mykyta Kachanov; Florian M. Wagenlehner (PLoS ONE, 2026)
Objective to investigate the effect of tumor location on oncological outcomes in patients receiving robot-assisted radical nephroureterectomy (RANU) for upper urinary tract carcinoma (UTUC). Methods A retrospective single-center cohort study of 54 patients with UTUC who underwent RANU by a single surgeon between July 2019 and July 2025, without neoadjuvant chemotherapy or previous or simultaneous cystectomy, were included. Patients were divided into two groups based on tumor location: 18 patients (33%) with ureteral tumors (Group 1) and 36 patients (67%) with renal pelvis tumors (Group 2). Demographics, perioperative data, and pathological results were analyzed. The primary endpoints Cancer-specific survival (CSS) and overall survival (OS) were estimated using Kaplan–Meier and univariable log-rank test. Results Console time, blood transfusion, complications, and readmission were comparable in both groups. Group 1 experienced longer hospital stays (8 days vs. 6.5 days, p = 0.03). 48% of patients had ≥ pT2 disease, with a similar T-stage distribution across groups. Of 26 candidates for adjuvant therapy, 10 received chemotherapy with gemcitabine/cisplatin, 2 received nivolumab, and one patient received enfortumab vedotin with pembrolizumab. During a median 26.5-month follow-up, six patients developed bladder recurrence, (median 9 months) after RANU (p = 0.10), and four developed distant metastases (median 4 months) (p = 0.72), resulting in a disease-free survival of 81% (p = 0.08)Cancer-specific survival was 94%, overall survival 89%, with no significant group differences (p = 0.24 and 0.49). Conclusion In our series, we observed that tumor location does not impact postoperative and oncological outcomes after RANU for UTUC, regardless of adjuvant therapy. However, further studies are needed to explore this proposed hypothesis.